INTIMATE LANGUAGE STYLE IN NICHOLAS SPARKS’ MOVIE SCRIPT THE NOTEBOOK - Annisa Octaviani; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2021)
This research is aimed at analyzing the intimate language style used by the characters in The Notebook movie. In this research, the characteristics of the intimate language style used by the characters and the factors that influence these figures using intimate language styles in the movie would be revealed. The researchers apply a descriptive qualitative design. The research data are in the forms of film transcripts. The main theory used in this research is the theory proposed by Martin Joos. The results show that the researchers find 22 intimate language style utterances. In detail, the 22 intimate language style utterances include Addresse with 6 data, Extraction with 4 data, Jargon 3 data, Close relationship with 5 data, and Family relationship with 4 data. In addition, it is also found that there are four social factors that influence the characters to use intimate language styles. The first factor is the participants. The film's participants have very close relationships such as Family members or Close friends. The second factor is topic. The topics discussed in this film are privacy and love. The third factor is setting. Conversations in the film are often completed in several informal and private places such as beaches, houses and so on. The fourth factor is function. The speech functions produced by these characters vary; however, most of them have the same aim; that is to convey or show their intimacy to each other.